Analysis of Yield Gaps in Black Gram (Vigna mungo) in Shimla District of Himachal Pradesh - Kumari, Neelam; Thakur, Ashok K.; Kaith, N.S. (International Journal of Economic Plants, 2020)
Blackgram (Vigna mungo) is an important pulse widely consumed in India. Area and production under this crop are declining in Shimla district of Himachal Pradesh due to non-adoption of improved varieties and recommended practices. Krishi Vigyan Kendra Shimla conducted cluster frontline demonstrations on blackgram with an objective to demonstrate and popularize the improved technologies on farmers’ fields for effective transfer and fill the gap between recommended practices and farmers’ practices. Frontline demonstrations on blackgram during Kharif season were studied for four years (Kharif 2016-17, Kharif 2017-18, Kharif 2018-19 and Kharif 2019-20) in Shimla district of Himachal Pradesh. Data revealed that there was a wide yield gap between the potential and demonstration yields mainly due ineffective transfer of technology. Increase in blackgram yield over farmers practice ranged from 7.22 to 54.84%over four years. Improved technology package has also improved the profitability of blackgram crop in terms of gross and net returns besides enhanced benefit cost ratio ranging from 1.62 to 2.68. The technology index in blackgram (13.20 to 36.00%) has revealed that demonstrated improved crop technology is feasible under prevailing farming situations in Shimla district of Himachal Pradesh, but there is urgent need to aware the farmers to adopt the technologically feasible and economically viable farm technologies.